Tundish cover castable
By using large-grain alumina and fine powder alumina in the castable material in the intermediate bag cover, and adding sintered mullite and other materials, the thermal shock damage and insufficient strength of the existing castable material was solved, and the heat was significantly improved The stability and strength of the earthquake extends the service life and reduces costs.
Patent Information
- Application Number
- CN202411490683.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-14
AI Technical Summary
The existing castable material for the intermediate bag cover is prone to thermal shock damage and insufficient strength under the high temperature impact of liquid steel, resulting in a short service life.
Use the reasonable combination of large-grain alumina and fine powder alumina, add sintered mullite, composite bonding agent, aluminum silicate, SiC nanowires and aluminum titanate to optimize the particle size ratio and composition ratio of the castable. To improve its thermal shock stability, compressive strength and flexural strength.
It significantly improves the thermal shock stability and strength of the castable material in the middle bag cover, reduces the thermal expansion coefficient and thermal conductivity coefficient, extends the service life, reaches more than 25 pouring times, and reduces production costs.
Smart Images

Figure BDA0005099962300000171 
Figure BDA0005099962300000181
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tundish refractory materials, and in particular relates to a tundish cover castable. Background Art
[0002] In the steel industry, the tundish is an indispensable part of the continuous casting process. Its function is to receive the molten steel poured from the ladle and achieve uniform and stable casting by regulating the flow of molten steel. As an important component of the tundish, the tundish cover is mainly responsible for heat preservation, preventing secondary oxidation of molten steel, and reducing heat loss. However, the tundish cover in the prior art generally has the problem of short service life, which not only increases production costs, but also affects the continuity and efficiency of continuous casting operations.
[0003] At present, the material of the tundish cover is mostly made of refractory castables. Although this material has certain high temperature resistance, in actual use, it is prone to thermal shock damage due to repeated high temperature impact of molten steel, resulting in structural deformation, castable peeling and other problems. According to statistics, the average service life of the tundish cover is mostly only 5 to 15 pourings, which is far lower than the ideal service life; in addition, the thermal expansion coefficient and thermal conductivity of the material at high temperature are large, which aggravates the degree of thermal shock damage and shortens the service life of the cover; at the same time, the frequent replacement of the tundish cover not only increases material consumption and processing costs, but also may affect the stable operation of the production line due to interruptions in the replacement process. Therefore, improving the thermal shock stability and high temperature strength of the tundish cover, while reducing its thermal expansion coefficient and thermal conductivity, has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] In view of the problems that the existing tundish cover castable causes thermal shock damage and insufficient strength under high-temperature impact of molten steel, and the thermal expansion coefficient and thermal conductivity coefficient of the material at high temperature are large, resulting in a short service life of the tundish cover, the present invention provides a tundish cover castable, which overcomes the defects of thermal shock damage and insufficient strength of traditional tundish cover castables, can significantly improve the thermal shock stability and strength of the tundish cover castable, reduce the thermal expansion coefficient and thermal conductivity coefficient, and effectively extend the service life of the tundish cover castable.
[0005] The solution adopted by the present invention to solve the technical problem is: a tundish cover castable, wherein the mass percentage of each raw material component in the tundish cover castable is: 8-5mm alumina is 7.8-9.6%, 5-3mm alumina is 2.6-4.3%, 1-0mm alumina is 2.6-4.3%, 200 mesh alumina is 17.4-20.8%, 5-3mm mullite is 9.6-13%, 3-1mm mullite is 22.6-26% , 1-0mm mullite is 9.6-13%, 200 mesh mullite is 7-8.7%, composite binder is 2.6-3.5%, aluminum silicate is 0.8-1.7%, SiC nanowire is 0.05-0.07%, aluminum titanate is 0.2-0.3%, alumina powder is 0.4-0.7%, sodium tripolyphosphate is 0.08-0.11%, silica fume is 2.6-3.5%, steel fiber is 0.87%, and high alumina cement is 1.3-1.7%.
[0006] Furthermore, in the tundish cover castable, the 8-5mm alumina is 8.4%, the 5-3mm alumina is 3.2%, the 1-0mm alumina is 3.6%, the 200-mesh alumina is 18.7%, the 5-3mm mullite is 11.4%, the 3-1mm mullite is 24.5%, the 1-0mm mullite is 11.8%, the 200-mesh mullite is 7.8%, the composite binder is 3.1%, the aluminum silicate is 1.2%, the SiC nanowire is 0.06%, the aluminum titanate is 0.24%, the alumina powder is 0.54%, the sodium tripolyphosphate is 0.09%, the silica fume is 3%, the steel fiber is 0.87%, and the high-alumina cement is 1.5%.
[0007] Furthermore, the Al2O3 content in the 8-5mm alumina is ≥80%; the Al2O3 content in the 5-3mm alumina is ≥80%; the Al2O3 content in the 1-0mm alumina is ≥85%; the Al2O3 content in the 200-mesh alumina is ≥87%; and the Al2O3 content in the high-alumina cement is ≥71%.
[0008] Furthermore, the mullite is sintered mullite; the particle size of aluminum silicate is 1250 mesh; the particle size of aluminum titanate is 800 mesh, industrial grade; the particle size of alumina micropowder is 1 μm; sodium tripolyphosphate is industrial grade; and the SiO2 content in silica ash is ≥95%.
[0009] Furthermore, the mass percentages of the raw material components in the composite binder are: polyacrylamide is 10%, silica sol is 90%, and the effective ingredient content of silica sol is 40%.
[0010] Furthermore, the sum of the mass percentages of 1-0 mm alumina and 1-0 mm mullite in the castable is 13-16%; the sum of the mass percentages of 200 mesh alumina and 200 mesh mullite is 24.5-28%.
[0011] Furthermore, the SiC nanowire has a diameter of 100-500 nm, a length of 50-100 um, a β-SiC crystal form, and is surface-modified with a silane coupling agent.
[0012] Furthermore, the surface modification treatment steps of the SiC nanowires are as follows:
[0013] (1) using ultrasonic waves to clean SiC nanowires in ethanol at a frequency of 20-30 kHz for 15-25 minutes, and drying them in an oven at a drying temperature of 100° C. for 1-2 hours;
[0014] (2) subjecting the dried SiC nanowires to surface oxidation treatment at a thermal oxidation temperature of 580-650° C. for 2 hours in an air atmosphere;
[0015] (3) treating the surface of the SiC nanowires after thermal oxidation treatment with a silane coupling agent at a concentration of 2-4% for 12 hours, and then drying at 100° C. for 2 hours;
[0016] (4) The SiC nanowires dried in step (3) are mechanically mixed in a ball mill at a speed of 200 rpm for 2 to 4 hours to obtain a finished product.
[0017] Furthermore, the castable is suitable for an electric furnace billet tundish (rectangular).
[0018] The present invention adopts a combination of large-particle alumina with a relatively low alumina content and fine-powder alumina with a relatively high alumina content, which can optimize the performance of the ladle castable. The large-particle alumina provides structural support and fluidity, while the fine-powder alumina enhances the density and chemical stability of the material. This alumina particle size combination enables the castable to withstand high temperatures and mechanical loads while maintaining good physical and chemical properties in a high-temperature environment, thereby meeting the special requirements of the continuous casting tundish cover during use; at the same time, this design can also balance cost and performance to achieve the dual goals of economic benefits and usage effects.
[0019] The present invention selects sintered mullite for addition because sintered mullite has excellent thermal stability, chemical stability, high temperature strength, corrosion resistance and good bonding performance, and can significantly improve the refractory performance, thermal stability and chemical stability of the ladle cover castable, thereby ensuring the safety and economy of the continuous casting process; the present invention selects mullite with different particle size distributions, 5-3mm and 3-1mm mullite can be used as the skeleton of the castable to provide necessary mechanical support, thereby improving the overall compressive strength and flexural strength of the castable, 1-0mm and 200 mesh mullite can fill the gaps between the skeleton particles, increase the density of the castable, and further improve its strength; at the same time, a reasonable particle size ratio helps to reduce the thermal conductivity of the castable and reduce heat transfer, thereby protecting the tundish cover from high temperature damage, thereby extending the service life of the tundish cover.
[0020] The composite binder (whose raw material components are composed of 10% polyacrylamide and 90% silica sol by mass) selected in the present invention has the following effects in preparing the tundish cover castable: first, the combination of polyacrylamide and silica sol not only brings into play the thickening and water retention properties of polyacrylamide, but also utilizes the high temperature stability and chemical activity of silica sol, so that the rheology, hardening speed, high temperature strength and corrosion resistance of the castable are improved; secondly, the addition of polyacrylamide improves the construction performance of the castable, so that it has better fluidity and thixotropy, is easy to pour and form, reduces the stratification and cracking that may occur during the construction process, and improves the construction efficiency and quality; thirdly, the use of the composite binder breaks through the limitations of a single binder and realizes the coordinated optimization of different performance indicators.
[0021] The effects of the 1250 mesh aluminum silicate selected in the present invention are mainly reflected in the following aspects: first, aluminum silicate has a relatively high melting point, which can significantly improve the refractory performance of the castable, ensure that the material maintains structural integrity at high temperatures, and resists the erosion of molten steel and slag; secondly, fine powdered aluminum silicate reduces the thermal conductivity of the castable, enhances thermal stability, enables the material to better adapt to rapid changes in temperature, and reduces the generation of thermal shock cracks; thirdly, the fine particles of aluminum silicate fill the gaps between large particles of the castable, improves the density of the material and the bonding force between particles, and enhances the overall strength; in addition, the low thermal conductivity of aluminum silicate makes it an excellent thermal insulation material, reduces the heat loss of the tundish cover, and improves the energy utilization efficiency; at the same time, aluminum silicate has a high thermal conductivity and a good thermal conductivity. It has good chemical stability at high temperatures and is not easy to react with chemicals in molten steel or slag, which reduces material erosion and extends the service life of the castable. Aluminum silicate has a low linear expansion coefficient, which helps to reduce the volume change of the castable during heating and cooling, reducing the risk of cracking. Improved construction performance: fine-grained aluminum silicate also improves the fluidity and construction performance of the castable, reduces the difficulty of construction, and forms a denser and more uniform casting structure with reduced porosity. In summary, the selection of 1250 mesh aluminum silicate is an optimal choice based on the balance of performance and cost-effectiveness, including improving the overall performance, fluidity and construction performance, bonding strength of the castable, reducing thermal conductivity, thermal shock cracks, and improving surface quality.
[0022] The present invention uses SiC nanowires surface-modified by silane coupling agents to bring about significant positive effects, which are mainly reflected in: first, the surface modification treatment by silane coupling agents significantly improves the interface bonding force between SiC nanowires and the matrix material, reduces interface defects, and thus enhances the overall composite strength; second, SiC nanowires are distributed in the castable, and when cracks begin to expand, the nanowires can play a "bridging" role, preventing crack expansion or changing the crack path, increasing energy consumption, and thus improving the toughness of the castable; in addition, the use of silane coupling agents can adjust the thermal expansion coefficient between SiC nanowires and the matrix material. The number of nanowires can reduce the internal stress caused by the difference in thermal expansion and contraction, and improve the thermal stability of the material; SiC nanowires form a reinforcing phase in the castable, especially at high temperatures, and can interact with the matrix material to form a more complex microstructure, further improving the comprehensive performance of the material; the presence of nanowires can also inhibit the grain growth of the matrix material at high temperatures to a certain extent, maintain the fine grain structure of the material, and is conducive to improving the high-temperature performance of the castable; at the same time, SiC itself has good thermal conductivity, and the addition of nanowires can improve the thermal conductivity of the castable, promote the rapid dissipation of heat, and reduce thermal stress. In summary, the introduction of SiC nanowires surface-modified by silane coupling agents not only significantly improves the mechanical strength, thermal stability and corrosion resistance of the intermediate ladle cover castable, but also optimizes the microstructure, enhances the interface bonding, and achieves a comprehensive improvement in material performance.
[0023] The present invention uses aluminum titanate to bring significant positive effects on the performance of the castable, and these effects are mainly derived from the characteristics of aluminum titanate itself and its interaction with the castable matrix, which are mainly reflected in: first, under high temperature conditions, aluminum titanate can induce microcracks, and these microcracks can consume the energy of crack expansion, play a toughening effect, and improve the fracture toughness of the castable; second, aluminum titanate, as a hard phase, can play a strengthening role in the castable, and can improve the hardness and strength of the material through a particle strengthening mechanism; third, the low thermal expansion coefficient of aluminum titanate helps to reduce the stress concentration caused by inconsistent thermal expansion inside the castable, thereby reducing the generation of cracks; in addition, there is a good interface bonding between aluminum titanate and the castable matrix, which can enhance the cohesion of the material, reduce defects at the interface, and improve the overall corrosion resistance and thermal shock resistance; at the same time, during the high-temperature sintering process, aluminum titanate can react with other components in the castable to form a more stable phase, promote the densification of the material, and improve its high-temperature performance. Therefore, by introducing aluminum titanate, the microstructure of the castable can be regulated, and the high-temperature stability, corrosion resistance, crack resistance and thermal expansion properties of the material can be improved through various mechanisms, thereby significantly improving the service life of the castable.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The present invention provides structural support and fluidity through the reasonable combination of large-particle alumina and fine-powder alumina, and enhances the density and chemical stability of the material, so that the castable can withstand high temperature and mechanical load, meet the special requirements of the continuous casting tundish cover, and balance the cost and performance;
[0026] 2. The present invention significantly improves the refractory performance, thermal stability and chemical stability of the castable by adding sintered mullite. The combination of mullite of different particle sizes enhances the overall compressive strength and flexural strength, reduces thermal conductivity, and prolongs the service life of the tundish cover;
[0027] 3. The present invention adopts a composite binder (polyacrylamide and silica sol) to improve the rheology, hardening speed, high temperature strength and corrosion resistance of the castable, improve the construction performance, reduce the delamination and cracking phenomenon, and achieve the coordinated optimization between different performance indicators;
[0028] 4. The present invention uses 1250 mesh aluminum silicate to improve the refractory performance of the castable, enhance thermal stability, reduce thermal shock cracks, improve density and overall strength, reduce heat loss, improve energy utilization efficiency, and extend the service life of the castable;
[0029] 5. The present invention uses SiC nanowires that have been surface-modified with a silane coupling agent, which significantly improves the interface bonding force with the matrix material, enhances the composite strength, prevents crack propagation, improves toughness, optimizes the microstructure, and improves thermal conductivity;
[0030] 6. The present invention introduces aluminum titanate, which significantly improves the high-temperature thermal shock stability, corrosion resistance, crack resistance and thermal expansion performance of the castable by inducing microcrack toughening, strengthening material hardness, reducing stress concentration, enhancing interface bonding and promoting material densification, thereby extending the service life of the castable.
[0031] In summary, compared with the traditional process, the tundish cover castable of the present invention significantly improves the overall performance of the tundish cover castable, including fire resistance, thermal shock stability, corrosion resistance, and construction performance, through material selection and ratio optimization. The flexural strength and compressive strength of the castable are also effectively enhanced, and the service life is significantly extended, reaching more than 25 pouring times, and the production cost is greatly saved, thereby improving the economy and operation rate of continuous casting operations. DETAILED DESCRIPTION
[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0033] The present invention provides a technical solution for a tundish cover castable:
[0034] A tundish cap casting material, wherein the mass percentages of the raw material components in the tundish cap casting material are: 8-5 mm alumina is 7.8-9.6%, 5-3 mm alumina is 2.6-4.3%, 1-0 mm alumina is 2.6-4.3%, 200 mesh alumina is 17.4-20.8%, 5-3 mm mullite is 9.6-13%, 3-1 mm mullite is 22.6-26%, 1-0 mm mullite ...200 mesh alumina is 17.4-20.8%, 5-3 mm mullite is 9.6-13%, 3-1 mm The raw materials include stone, 9.6-13%, 200-mesh mullite, 7-8.7%, composite binder, 2.6-3.5%, aluminum silicate, 0.8-1.7%, SiC nanowire, 0.05-0.07%, aluminum titanate, 0.2-0.3%, alumina powder, 0.4-0.7%, sodium tripolyphosphate, 0.08-0.11%, silica fume, 2.6-3.5%, steel fiber, and 1.3-1.7% high alumina cement.
[0035] As a preferred embodiment of the present invention, the tundish cover castable comprises 8.4% 8-5mm alumina, 3.2% 5-3mm alumina, 3.6% 1-0mm alumina, 18.7% 200-mesh alumina, 11.4% 5-3mm mullite, 24.5% 3-1mm mullite, 11.8% 1-0mm mullite, 7.8% 200-mesh mullite, 3.1% composite binder, 1.2% aluminum silicate, 0.06% SiC nanowire, 0.24% aluminum titanate, 0.54% alumina powder, 0.09% sodium tripolyphosphate, 3% silica ash, 0.87% steel fiber and 1.5% high alumina cement.
[0036] As a preferred embodiment of the present invention, the Al2O3 content in the 8-5mm alumina is ≥80%; the Al2O3 content in the 5-3mm alumina is ≥80%; the Al2O3 content in the 1-0mm alumina is ≥85%; the Al2O3 content in the 200-mesh alumina is ≥87%; and the Al2O3 content in the high-alumina cement is ≥71%.
[0037] The present invention adopts a combination of large-particle alumina with a relatively low alumina content and fine-powder alumina with a relatively high alumina content, which can achieve the optimization of the performance of the cover castable. The large-particle alumina provides structural support and fluidity, while the fine-powder alumina enhances the density and chemical stability of the material. This alumina particle size combination enables the castable to withstand high temperature and mechanical loads, and maintain good physical and chemical properties in a high-temperature environment, thereby meeting the special requirements of the continuous casting tundish cover during use; at the same time, the use of high-alumina cement with a high Al2O3 content can improve the high-temperature resistance of the overall material, making it more suitable for use in a high-temperature environment, and can also enhance the overall strength and crack resistance of the castable to a certain extent.
[0038] As a preferred embodiment of the present invention, the mullite is sintered mullite; the aluminum silicate particle size is 1250 mesh; the aluminum titanate particle size is 800 mesh, industrial grade; the alumina micropowder particle size is 1 μm; the sodium tripolyphosphate is industrial grade; the SiO2 content in the silica ash is ≥95%.
[0039] The present invention uses 1250 mesh aluminum silicate, which can improve the refractory performance through its high melting point, reduce thermal conductivity and enhance thermal stability through fine powder aluminum silicate, improve density and strength through filling the gaps of the castable with fine particles, achieve excellent thermal insulation through low thermal conductivity, reduce material erosion through high temperature chemical stability, reduce the risk of cracking of the castable through low linear expansion coefficient, improve construction performance and form a dense structure, etc., and comprehensively optimize the performance and service life of the castable; by introducing 800 mesh aluminum titanate, it is used to induce microcracks and toughen, and further improve the fracture toughness of the castable. Crack toughness, the hard phase particle strengthening mechanism can further improve the strength and hardness of the castable, the low thermal expansion coefficient helps to reduce the internal stress concentration of the castable, further reduce the generation of cracks, good interface bonding enhances cohesion, improves the overall corrosion resistance and thermal shock resistance, high temperature sintering promotes densification and improves high temperature performance, thereby greatly improving its service life; the use of alumina micropowder with a particle size of 1μm can significantly improve the comprehensive performance of the tundish cover castable, because its fine particles can more effectively fill the pores, enhance density, optimize mechanical properties, and improve hardness and strength, and by reducing thermal stress and promoting the sintering process, enhancing thermal shock resistance and erosion resistance, thereby ensuring that the castable has a longer service life and more stable performance; the present invention adopts a high content of SiO2, which can react well with other components in the castable to form a stable silicate network structure, which not only improves the mechanical strength and wear resistance of the castable, but also significantly enhances its ability to resist alkali erosion and sulfate erosion. In addition, the fine particles of silica fume can effectively fill the tiny pores in the castable, reduce the porosity, and thus improve the density of the castable In high temperature environment, this castable shows excellent thermal stability and thermal shock resistance, ensuring the structural integrity and service life of the tundish cover during repeated heating and cooling; when aluminum titanate and sodium tripolyphosphate are used as industrial-grade additives to prepare the tundish cover castable, they can significantly improve the castable's wear resistance, thermal stability, thermal shock resistance and erosion resistance. At the same time, by promoting sintering and improving construction performance, the service life of the castable is effectively extended, ensuring that it maintains excellent performance in high temperature environment, thereby improving the overall durability and work efficiency of the tundish.
[0040] As a preferred embodiment of the present invention, the mass percentages of the raw material components in the composite binder are: polyacrylamide is 10%, silica sol is 90%, and the effective ingredient content of silica sol is 40%.
[0041] The composite binder of the present invention adopts the combination of polyacrylamide and silica sol, and the specific ratio of 10% polyacrylamide to 90% silica sol is the optimal formula determined on the basis of a large number of experiments and theoretical studies. It balances the relationship between cost, construction performance and final product performance, and not only exerts the thickening and water retention characteristics of polyacrylamide, but also utilizes the high temperature stability and chemical activity of silica sol, so that the rheological properties, hardening speed, high temperature strength and corrosion resistance of the castable are improved; silica sol, as a low-viscosity colloidal solution, has good adhesion, and its nano-scale micelles can be fully immersed in and filled into solid objects, so that the various components of the castable are closely combined. Polyacrylamide, as a thickener, can further enhance the bonding effect, thereby improving the overall strength of the castable, and the high-efficiency components of silica sol improve the high temperature resistance and thermal shock resistance of the castable, thereby ensuring the long-term stable use and excellent protective performance of the cover in a high temperature environment.
[0042] As a preferred embodiment of the present invention, the sum of the mass percentages of 1-0 mm alumina and 1-0 mm mullite in the castable is 13-16%; the sum of the mass percentages of 200 mesh alumina and 200 mesh mullite is 24.5-28%.
[0043] The present invention can optimize the particle gradation of the castable by controlling the ratio of alumina and mullite of different particle sizes, so that the castable is more densely packed and the porosity is reduced, thereby improving the density and strength of the castable. Reasonable particle gradation helps to disperse and relieve thermal stress, reduce cracks and peeling caused by rapid temperature changes, thereby improving the thermal shock resistance of the castable; coarser particles (1-0mm) can provide better wear resistance and erosion resistance, while finer particles (200 mesh) help fill pores and improve overall corrosion resistance. This combination enables the castable to exhibit more excellent performance when subjected to the corrosion of high-temperature slag and molten metal; at the same time, by optimizing the particle gradation, the overall performance of the castable, including strength, toughness, wear resistance, corrosion resistance and thermal shock resistance, can be comprehensively improved, thereby extending the service life of the tundish cover, reducing the number of repairs and replacements, and reducing production costs.
[0044] As a preferred embodiment of the present invention, the SiC nanowire has a diameter of 100-500 nm, a length of 50-100 um, a crystalline form of β-SiC, and is surface-modified with a silane coupling agent.
[0045] As a preferred embodiment of the present invention, the surface modification treatment steps of SiC nanowires are as follows:
[0046] (1) using ultrasonic waves to clean SiC nanowires in ethanol at a frequency of 20-30 kHz for 15-25 minutes, and drying them in an oven at a drying temperature of 100° C. for 1-2 hours;
[0047] (2) subjecting the dried SiC nanowires to surface oxidation treatment at a thermal oxidation temperature of 580-650° C. for 2 hours in an air atmosphere;
[0048] (3) treating the surface of the SiC nanowires after thermal oxidation treatment with a silane coupling agent at a concentration of 2-4% for 12 hours, and then drying at 100° C. for 2 hours;
[0049] (4) The SiC nanowires dried in step (3) are mechanically mixed in a ball mill at a speed of 200 rpm for 2 to 4 hours to obtain a finished product.
[0050] The present invention selects SiC nanowires that have been surface-modified with a silane coupling agent, which significantly improves the interface bonding force between the SiC nanowires and the matrix material, reduces interface defects, and thus enhances the overall composite strength; secondly, the SiC nanowires are distributed in the castable, and when cracks begin to expand, the nanowires can play a "bridging" role, preventing the cracks from expanding or changing the crack path, increasing energy consumption, and thus improving the toughness of the castable; in addition, the use of the silane coupling agent can adjust the thermal expansion coefficient between the SiC nanowires and the matrix material, reduce the internal stress caused by the difference in thermal expansion and contraction, and improve the thermal stability of the material; the SiC nanowires form a reinforcing phase in the castable, especially at high temperatures, and can interact with the matrix material to form a more complex microstructure, further improving the comprehensive performance of the material; the presence of the nanowires can also inhibit the grain growth of the matrix material at high temperatures to a certain extent, maintain the fine grain structure of the material, and is conducive to improving the high-temperature performance of the castable; at the same time, SiC itself has good thermal conductivity, and the addition of the nanowires can improve the thermal conductivity of the castable, promote the rapid dissipation of heat, and reduce thermal stress.
[0051] As a preferred embodiment of the present invention, the castable is suitable for an electric furnace billet tundish (rectangular).
[0052] Specific implementation cases:
[0053] A specific embodiment of a tundish cover castable of the present invention is provided below.
[0054] Embodiment 1:
[0055] The present embodiment provides a tundish cover castable, wherein the tundish cover castable has the following components in percentage by mass: 8.4% alumina of 8-5 mm, 3.2% alumina of 5-3 mm, 3.6% alumina of 1-0 mm, 18.7% alumina of 200 mesh, 11.4% mullite of 5-3 mm, 24.5% mullite of 3-1 mm, 11.8% mullite of 1-0 mm, 7.8% mullite of 200 mesh, 3.1% composite binder, 1.2% aluminum silicate, 0.06% SiC nanowire, 0.24% aluminum titanate, 0.54% alumina powder, 0.09% sodium tripolyphosphate, 3% silica fume, 0.87% steel fiber, and 1.5% high alumina cement.
[0056] In addition, the present invention uses a silane coupling agent to modify the surface of the SiC nanowires, and the processing steps are:
[0057] (1) using ultrasound to clean the SiC nanowires in ethanol at a frequency of 20-30 kHz for 25 minutes, and drying them in an oven at a drying temperature of 100° C. for 1 hour;
[0058] (2) subjecting the dried SiC nanowires to surface oxidation treatment at a thermal oxidation temperature of 650° C. for 2 hours in an air atmosphere;
[0059] (3) treating the surface of the SiC nanowires after thermal oxidation treatment with a silane coupling agent at a concentration of 2-4% for 12 hours, and then drying at 100° C. for 2 hours;
[0060] (4) The SiC nanowires dried in step (3) were mechanically mixed in a ball mill at a speed of 200 rpm for 4 hours to obtain a finished product.
[0061] Embodiment 2:
[0062] The present embodiment provides a tundish cover castable, wherein the tundish cover castable has the following components in percentage by mass: 8% alumina of 8-5 mm, 3.6% alumina of 5-3 mm, 2.6% alumina of 1-0 mm, 17.8% alumina of 200 mesh, 13% mullite of 5-3 mm, 24.1% mullite of 3-1 mm, 12.4% mullite of 1-0 mm, 8.7% mullite of 200 mesh, 2.9% composite binder, 0.9% aluminum silicate, 0.07% SiC nanowire, 0.3% aluminum titanate, 0.66% alumina powder, 0.1% sodium tripolyphosphate, 2.6% silica fume, 0.87% steel fiber, and 1.4% high alumina cement.
[0063] In addition, the present invention uses a silane coupling agent to modify the surface of the SiC nanowires, and the processing steps are:
[0064] (1) using ultrasound to clean the SiC nanowires in ethanol at a frequency of 20-30 kHz for 15 minutes, and drying them in an oven at a drying temperature of 100° C. for 2 hours;
[0065] (2) subjecting the dried SiC nanowires to surface oxidation treatment at a thermal oxidation temperature of 580° C. for 2 hours in an air atmosphere;
[0066] (3) treating the surface of the SiC nanowires after thermal oxidation treatment with a silane coupling agent at a concentration of 2-4% for 12 hours, and then drying at 100° C. for 2 hours;
[0067] (4) The SiC nanowires dried in step (3) were mechanically mixed in a ball mill at a speed of 200 rpm for 2 hours to obtain a finished product.
[0068] Embodiment 3:
[0069] The present embodiment provides a tundish cover castable, and the tundish cover castable has the following components in percentage by mass: 8-5mm alumina is 9.6%, 5-3mm alumina is 2.8%, 1-0mm alumina is 3.7%, 200-mesh alumina is 20.8%, 5-3mm mullite is 10%, 3-1mm mullite is 25.7%, 1-0mm mullite is 9.6%, 200-mesh mullite is 7%, composite binder is 3.2%, aluminum silicate is 0.8%, SiC nanowire is 0.06%, aluminum titanate is 0.26%, aluminum oxide powder is 0.7%, sodium tripolyphosphate is 0.11%, silica fume is 3.3%, steel fiber is 0.87%, and high alumina cement is 1.5%.
[0070] In addition, the present invention uses a silane coupling agent to modify the surface of the SiC nanowires, and the processing steps are:
[0071] (1) using ultrasound to clean the SiC nanowires in ethanol at a frequency of 20-30 kHz for 25 minutes, and drying them in an oven at a drying temperature of 100° C. for 2 hours;
[0072] (2) subjecting the dried SiC nanowires to surface oxidation treatment at a thermal oxidation temperature of 650° C. for 2 hours in an air atmosphere;
[0073] (3) treating the surface of the SiC nanowires after thermal oxidation treatment with a silane coupling agent at a concentration of 2-4% for 12 hours, and then drying at 100° C. for 2 hours;
[0074] (4) The SiC nanowires dried in step (3) were mechanically mixed in a ball mill at a speed of 200 rpm for 4 hours to obtain a finished product.
[0075] Embodiment 4:
[0076] The present embodiment provides a tundish cap castable material, wherein the tundish cap castable material has the following components in percentage by mass: 8.2% of 8-5mm alumina, 4.3% of 5-3mm alumina, 2.8% of 1-0mm alumina, 17.4% of 200-mesh alumina, 12.5% of 5-3mm mullite, 23.7% of 3-1mm mullite, 13% of 1-0mm mullite, 7.3% of 200-mesh mullite, 3.5% of composite binder, 1% of aluminum silicate, 0.05% of SiC nanowires, 0.22% of aluminum titanate, 0.58% of alumina powder, 0.08% of sodium tripolyphosphate, 2.8% of silica fume, 0.87% of steel fiber, and 1.7% of high-alumina cement. Other conditions are the same, and the surface modification treatment steps of SiC nanowires are the same as those in Example 1.
[0077] Embodiment 5:
[0078] The present embodiment provides a tundish cap castable material, wherein the tundish cap castable material has the following components in percentage by mass: 8-5 mm alumina is 7.8%, 5-3 mm alumina is 4%, 1-0 mm alumina is 4.3%, 200 mesh alumina is 20%, 5-3 mm mullite is 11.2%, 3-1 mm mullite is 22.6%, 1-0 mm mullite is 10.7%, 200 mesh mullite is 8%, composite binder is 2.8%, aluminum silicate is 1.7%, SiC nanowire is 0.07%, aluminum titanate is 0.2%, aluminum oxide powder is 0.67%, sodium tripolyphosphate is 0.09%, silica fume is 3.5%, steel fiber is 0.87%, and high alumina cement is 1.5%. Other conditions are the same, and the surface modification treatment steps of SiC nanowire are the same as those in Example 1.
[0079] Embodiment 6:
[0080] The present embodiment provides a tundish cap castable material, wherein the tundish cap castable material has the following components in percentage by mass: 8-5 mm alumina is 9%, 5-3 mm alumina is 2.6%, 1-0 mm alumina is 4%, 200 mesh alumina is 20.1%, 5-3 mm mullite is 9.6%, 3-1 mm mullite is 26%, 1-0 mm mullite is 11.5%, 200 mesh mullite is 7.2%, composite binder is 2.6%, aluminum silicate is 1.3%, SiC nanowire is 0.05%, aluminum titanate is 0.28%, aluminum oxide powder is 0.4%, sodium tripolyphosphate is 0.1%, silica fume is 3.1%, steel fiber is 0.87%, and high alumina cement is 1.3%. Other conditions are the same, and the surface modification treatment steps of SiC nanowire are the same as those in Example 1.
[0081] Comparative Example 1:
[0082] The comparative example provides a tundish cover castable, wherein the tundish cover castable comprises the following components in percentage by mass: 8% alumina of 8-5 mm, 3.6% alumina of 5-3 mm, 2.6% alumina of 1-0 mm, 17.8% alumina of 200 mesh, 13% mullite of 5-3 mm, 24.1% mullite of 3-1 mm, 12.4% mullite of 1-0 mm, 2.6% mullite of 200 mesh, 1.8% mullite of 200 mesh, 1.6% mullite of 3-1 mm, 1.5% mullite of 10-20 mm, 1.6% mullite of 200 mesh, 1.8% mullite of 200 mesh, 1.9% mullite of 3-1 mm, 2.9% mullite of 10-20 mm, 2.6% mullite of 200 mesh, 2.6% mullite of 200 mesh, 1.8% mullite of 5-3 mm, 2.6% mullite of 200 mesh, 1.6% mullite of 200 mesh, 1.8% mullite of 200 mesh, 1.6 ... 00 mesh mullite is 8.7%, composite binder is 2.9%, aluminum silicate is 0.9%, SiC nanowire is 0.07%, aluminum titanate is 0.3%, alumina powder is 0.66%, sodium tripolyphosphate is 0.1%, silica fume is 2.6%, steel fiber is 0.87%, high alumina cement is 1.4%, and the surface modification treatment steps of SiC nanowire are the same as those in the above embodiment. In this comparative example, the composite binder is all silica sol.
[0083] Comparative Example 2:
[0084] The present comparative example provides a tundish cover castable, wherein the tundish cover castable has the following components in percentage by mass: 8-5 mm alumina is 9.6%, 5-3 mm alumina is 3.6%, 1-0 mm alumina is 3.7%, 200 mesh alumina is 20.8%, 5-3 mm mullite is 10%, 3-1 mm mullite is 25.7%, 1-0 mm mullite is 9.6%, 200 mesh mullite is 7%, composite binder is 3.2%, SiC nanowire is 0.06%, aluminum titanate is 0.26%, alumina powder is 0.7%, sodium tripolyphosphate is 0.11%, silica fume is 3.3%, steel fiber is 0.87%, high alumina cement is 1.5%, the surface modification treatment steps of SiC nanowire are the same as those in the above embodiment, and this comparative example does not contain aluminum silicate.
[0085] Comparative Example 3:
[0086] The comparative example provides a tundish cover castable, and the tundish cover castable has the following components in percentage by mass: 8.25% alumina of 8-5 mm, 4.3% alumina of 5-3 mm, 2.8% alumina of 1-0 mm, 17.4% alumina of 200 mesh, 12.5% mullite of 5-3 mm, 23.7% mullite of 3-1 mm, 13% mullite of 1-0 mm, 7.3% mullite of 200 mesh, 3.5% composite binder, 1% aluminum silicate, 0.22% aluminum titanate, 0.58% alumina powder, 0.08% sodium tripolyphosphate, 2.8% silica fume, 0.87% steel fiber, and 1.7% high alumina cement. The comparative example does not contain SiC nanowires.
[0087] Comparative Example 4:
[0088] The present comparative example provides a tundish cover castable, wherein the tundish cover castable has the following components in percentage by mass: 8% alumina of 8-5 mm, 4% alumina of 5-3 mm, 4.3% alumina of 1-0 mm, 20% alumina of 200 mesh, 11.2% mullite of 5-3 mm, 22.6% mullite of 3-1 mm, 10.7% mullite of 1-0 mm, 8% mullite of 200 mesh, 2.8% composite binder, 1.7% aluminum silicate, 0.07% SiC nanowire, 0.67% alumina powder, 0.09% sodium tripolyphosphate, 3.5% silica fume, 0.87% steel fiber, 1.5% high alumina cement, the surface modification treatment steps of SiC nanowire are the same as those in the above embodiment, and the present comparative example does not contain aluminum titanate.
[0089] In the present invention, the sample preparation of a tundish cover castable of Examples 1 to 6 and Comparative Examples 1 to 4 is carried out according to GB / T4513.5-2017 "Monomorphous Refractory Materials Part 5: Sample Preparation and Pretreatment" to prepare specimens, and the tests of bulk density, linear change rate, flexural strength and compressive strength are carried out according to the test method in GB / T 4513.6-2017 "Monomorphous Refractory Materials Part 6: Determination of Physical Properties", and the casting times are used on a 50-ton tundish (rectangular) of an electric furnace billet for statistics.
[0090] The inspection index range of qualified products is: water addition rate is 5.5-6.2wt%; solidification time is 1-3h; the sum of the mass percentage of 1-0mm alumina and 1-0mm mullite is 13-16%; the sum of the mass percentage of 200 mesh alumina and 200 mesh mullite is 24.5-28%; the bulk density is 2.5-2.7g·cm 3; Linear change rate (1100℃ / 3h) is -0.2~0.15%, Linear change rate (1600℃ / 3h) is 0~0.5%; Flexural strength (110℃) is ≥8.5MPa, Flexural strength (1100℃ / 3h) is ≥11.5MPa, Flexural strength (1600℃ / 3h) is ≥11.5MPa; Compressive strength (110℃) is ≥50MPa, Compressive strength (1100℃ / 3h) is ≥85MPa, Compressive strength (1600℃ / 3h) is ≥95MPa; Use pouring times is ≥25 times; Construction performance is good. Test results are shown in Table 1:
[0091] Table 1 Test results of Examples 1 to 6 and Comparative Examples 1 to 4
[0092]
[0093]
[0094] Comparative Example 1 is based on Example 2, in which the introduction of polyacrylamide is cancelled in the composite binder, and all of it is silica sol. As can be seen from Table 1, compared with Example 2, the water addition rate and solidification time of Comparative Example 1 are significantly increased, the linear change rate at 1100°C / 3h is too large, and the flexural strength and compressive strength are significantly reduced. It is only used for 18 teaching times, the construction performance is general, and the test results are unqualified. The test effect of Comparative Example 1 is significantly lower than that of Example 2.
[0095] Comparative Example 2 is based on Example 3, but the introduction of aluminum silicate is cancelled and 5-3 mm of alumina is correspondingly increased. As can be seen from Table 1, compared with Example 3, the flexural strength, compressive strength and number of castings of Comparative Example 2 are all reduced, among which the compressive strength at 1100°C / 3h is too low, and the test result is unqualified. The test effect of Comparative Example 2 is significantly lower than that of Example 3.
[0096] Comparative Example 3 is based on Example 4, but the introduction of SiC nanowires is cancelled, and 8-5 mm of alumina is correspondingly added. As can be seen from Table 1, compared with Example 4, the flexural strength and compressive strength of Comparative Example 3 are reduced, among which the flexural strength at 1600°C / 3h and the compressive strength at 1600°C / 3h are too low, the number of castings is significantly reduced, and the test results are unqualified. The test effect of Comparative Example 3 is significantly lower than that of Example 4.
[0097] Comparative Example 4 is based on Example 5, but the introduction of aluminum titanate is cancelled, and 8-5mm alumina is correspondingly added. As can be seen from Table 1, compared with Example 5, the flexural strength and compressive strength of Comparative Example 4 are reduced, among which the linear change rate at 1600℃ / 3h is too large, the flexural strength at 1600℃ / 3h and the compressive strength at 1600℃ / 3h are too low, the number of castings is significantly reduced, and the test results are unqualified. The test effect of Comparative Example 4 is significantly lower than that of Example 5.
[0098] In summary, the present invention can effectively improve the flexural strength and compressive strength of the tundish cover castable by adding aluminum silicate, SiC nanowires and aluminum titanate, and the service life is significantly increased. By adding a composite binder combining polyacrylamide and silica sol, the thickening and water retention properties of polyacrylamide are brought into play, and the high temperature stability and chemical activity of silica sol are also utilized, so that the rheology, hardening speed, high temperature strength and corrosion resistance of the castable are improved, thereby reducing production costs and improving product quality.
[0099] The above description is only a preferred embodiment of the present invention and does not limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A tundish cover casting material, characterized in that: The mass percentages of the raw material components in the tundish cover casting material are as follows: 8-5 mm alumina is 7.8-9.6%, 5-3 mm alumina is 2.6-4.3%, 1-0 mm alumina is 2.6-4.3%, 200 mesh alumina is 17.4-20.8%, 5-3 mm mullite is 9.6-13%, 3-1 mm mullite is 22.6-26%, 1-0 mm mullite is 9.6- 13%, 200 mesh mullite is 7-8.7%, composite binder is 2.6-3.5%, aluminum silicate is 0.8-1.7%, SiC nanowire is 0.05-0.07%, aluminum titanate is 0.2-0.3%, alumina powder is 0.4-0.7%, sodium tripolyphosphate is 0.08-0.11%, silica fume is 2.6-3.5%, steel fiber is 0.87%, and high alumina cement is 1.3-1.7%.
2. The tundish cover casting material according to claim 1, characterized in that: The tundish cover castable contains 8.4% of 8-5mm alumina, 3.2% of 5-3mm alumina, 3.6% of 1-0mm alumina, 18.7% of 200-mesh alumina, 11.4% of 5-3mm mullite, 24.5% of 3-1mm mullite, 11.8% of 1-0mm mullite, 7.8% of 200-mesh mullite, 3.1% of composite binder, 1.2% of aluminum silicate, 0.06% of SiC nanowires, 0.24% of aluminum titanate, 0.54% of alumina powder, 0.09% of sodium tripolyphosphate, 3% of silica fume, 0.87% of steel fiber and 1.5% of high-alumina cement.
3. The tundish cover casting material according to claim 1, characterized in that: The Al2O3 content in the 8-5mm alumina is ≥80%; the Al2O3 content in the 5-3mm alumina is ≥80%; the Al2O3 content in the 1-0mm alumina is ≥85%; the Al2O3 content in the 200-mesh alumina is ≥87%; and the Al2O3 content in the high-alumina cement is ≥71%.
4. The tundish cover casting material according to claim 1, characterized in that: The mullite is sintered mullite; the particle size of aluminum silicate is 1250 mesh; the particle size of aluminum titanate is 800 mesh, industrial grade; the particle size of alumina micropowder is 1 μm; sodium tripolyphosphate is industrial grade; the SiO2 content in silica ash is ≥95%.
5. The tundish cover casting material according to claim 1, characterized in that: The mass percentages of the raw material components in the composite binder are as follows: polyacrylamide is 10%, silica sol is 90%, and the effective component content of silica sol is 40%.
6. The tundish cover casting material according to claim 1, characterized in that: The sum of the mass percentages of 1-0mm alumina and 1-0mm mullite in the castable is 13-16%; the sum of the mass percentages of 200-mesh alumina and 200-mesh mullite is 24.5-28%.
7. The tundish cover casting material according to claim 1, characterized in that: The SiC nanowire has a diameter of 100-500nm, a length of 50-100um, a β-SiC crystal form, and is surface-modified by a silane coupling agent.
8. The tundish cover casting material according to claim 7, characterized in that: The SiC nanowire surface modification treatment steps are: (1) using ultrasonic waves to clean SiC nanowires in ethanol at a frequency of 20-30 kHz for 15-25 minutes, and drying them in an oven at a drying temperature of 100° C. for 1-2 hours; (2) subjecting the dried SiC nanowires to surface oxidation treatment at a thermal oxidation temperature of 580-650° C. for 2 hours in an air atmosphere; (3) treating the surface of the SiC nanowires after thermal oxidation treatment with a silane coupling agent at a concentration of 2-4% for 12 hours, and then drying at 100° C. for 2 hours; (4) The SiC nanowires dried in step (3) are mechanically mixed in a ball mill at a speed of 200 rpm for 2 to 4 hours to obtain a finished product.
9. The tundish cover casting material according to claim 1, characterized in that: The castable is suitable for electric furnace billet tundish (rectangular).
Citation Information
Patent Citations
Castable for steel ladle cover and application thereof
CN103979949A
Ceramic fiber refractory castable and preparation method thereof
CN109553428A
Tundish castable and preparation method thereof
CN111377715A
Light high-strength refractory castable for steel ladle cover as well as preparation method and application thereof
CN115159996A
Silicon carbide-based castable for repairing carbonaceous furnace hole brick and preparation method of silicon carbide-based castable
CN115403391A
Cited By
Castable based on silica sol cooperating with aluminum titanate as well as preparation method and application of castable
CN121181341A
Silica sol and aluminum titanate based castable, preparation method and application thereof
CN121181341B